The British Approach to Monopoly Control - Harbury, C. D.; Raskind, Leo J. (Quarterly Journal of Economics, 1953)
Introduction, 380. — I. Duties and procedures of the Commission, 381. — II. Dental Report, 383. — III. Rainwater Report, 388. — IV. Lamps Report, 391. — V. Electric Wire and Cables Report and Insulin Report, 395. — VI. Matches and Match-Making Machinery Report, 397. — VII. Conclusion, 402.